Cognitive control, cognitive reserve, and memory in the aging bilingual brain - Grant, Angela; Dennis, Nancy A.; Li, Ping (Frontiers in Psychology, 2014)
In recent years bilingualism has been linked to both advantages in executive control and positive impacts on aging. Such positive cognitive effects of bilingualism have been attributed to the increased need for language control during bilingual processing and increased cognitive reserve, respectively. However, a mechanistic explanation of how bilingual experience contributes to cognitive reserve is still lacking. The current paper proposes a new focus on bilingual memory as an avenue to explore the relationship between executive control and cognitive reserve. We argue that this focus will enhance our understanding of the functional and structural neural mechanisms underlying bilingualism-induced cognitive effects. With this perspective we discuss and integrate recent cognitive and neuroimaging work on bilingual advantage, and suggest an account that links cognitive control, cognitive reserve, and brain reserve in bilingual aging and memory.